A transferable plasticity region in Campylobacter coli allows isolates of an otherwise non‐glycolytic food‐borne pathogen to catabolize glucose. Issue 5 (10th September 2015) - Vorwerk, Hanne; Huber, Claudia; Mohr, Juliane; Bunk, Boyke; Bhuju, Sabin; Wensel, Olga; Spröer, Cathrin; Fruth, Angelika; Flieger, Antje; Schmidt‐Hohagen, Kerstin; Schomburg, Dietmar; Eisenreich, Wolfgang; et al.
Summary: Thermophilic C ampylobacter species colonize the intestine of agricultural and domestic animals commensally but cause severe gastroenteritis in humans. In contrast to other enteropathogenic bacteria, Campylobacter has been considered to be non‐glycolytic, a metabolic property originally used for their taxonomic classification. Contrary to this dogma, we demonstrate that several C ampylobacter coli strains are able to utilize glucose as a growth substrate. Isotopologue profiling experiments with 13 C‐labeled glucose suggested that these strains catabolize glucose via the pentose phosphate and Entner‐Doudoroff (ED) pathways and use glucose efficiently for de novo synthesis of amino acids and cell surface carbohydrates. Whole genome sequencing of glycolytic C . coli isolates identified a genomic island located within a ribosomal RNA gene cluster that encodes for all ED pathway enzymes and a glucose permease. We could show in vitro that a non‐glycolytic C . coli strain could acquire glycolytic activity through natural transformation with chromosomal DNA of C . coli and C . jejuni subsp. doylei strains possessing the ED pathway encoding plasticity region. These results reveal for the first time the ability of a Campylobacter species to catabolize glucose and provide new insights into how genetic macrodiversity through intra‐ and interspecies gene transfer expand the metabolic capacity of this food‐borne pathogen. Abstract : Food‐borne Campylobacter are assumed to be non‐glycolytic pathogens, a metabolic characteristic distinguishing them from other enteropathogenic bacteria. In contrast to this dogma, we demonstrate for the first time that certain Campylobacter coli strains can catabolize glucose. This glycolytic property depends on the presence of a genomic island that can be spread by horizontal gene transfer and encodes for a glucose permease and all enzymes required for the degradation of glucose through the Entner‐Doudoroff pathway.